OnabotulinumtoxinA and Hyaluronic Acid in Facial Wrinkles and Folds: A Prospective, Open-Label Comparison. (11th May 2018) - Cohen, Joel L; Swift, Arthur; Solish, Nowell; Fagien, Steve; Glaser, Dee Anna
Abstract: Background: OnabotulinumtoxinA and hyaluronic acid are effective in improving moderate to severe facial wrinkles and folds, with treatment selection traditionally based upon facial area. Objectives: This prospective, multicenter, open-label, crossover study evaluated physician-rated efficacy and patient-rated outcomes following moderate to severe facial wrinkles and folds treatment with onabotulinumtoxinA and hyaluronic acid. Methods: 152 subjects (25-65 years) were randomized (1:1) to a treatment-sequence of onabotulinumtoxinA/hyaluronic acid or hyaluronic acid/onabotulinumtoxinA, with initial treatment administered on day 1 and 6 additional visits: week 2 (touch-up); week 4 (crossover); week 6 (touch-up); and weeks 8, 12, and 24 (follow-up). Results: Between 92% and 100% of subjects in each treatment-sequence group exhibited at least some improvement from baseline at each study visit in the Physician Aesthetic Improvement Scale and the Objective Observer and Patient Global Assessments of Improvement, with no significant between-sequence differences. Subjects reported looking 3 to 6 years younger at each visit, with significant improvements in glabellar, lateral canthal, and horizontal forehead lines, and nasolabial folds. Treatments were well tolerated. Conclusions: OnabotulinumtoxinA and hyaluronic acid provide clinically meaningful improvements as rated by physicians, objective observers, and subjects, with clinical synergy in aesthetic effects and duration of response regardless of treatment administration order in subjects seeking improvement in moderate to severe facial wrinkles and folds. Level of Evidence: 2: